2004
DOI: 10.1158/0008-5472.can-03-1101
|View full text |Cite
|
Sign up to set email alerts
|

Energy Substrate Modulates Mitochondrial Structure and Oxidative Capacity in Cancer Cells

Abstract: Comparative analysis of cytoplasmic organelles in a variety of tumors relative to normal tissues generally reveals a strong diminution in mitochondrial content and in oxidative phosphorylation capacity. However, little is known about what triggers these modifications and whether or not they are physiologically reversible. We hypothesized that energy substrate availability could play an important role in this phenomenon. The physiological effects of a change in substrate availability were examined on a human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
593
2
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 743 publications
(670 citation statements)
references
References 39 publications
61
593
2
14
Order By: Relevance
“…We believe the higher detection rate for the mtDNA 4977 mutation in our study is a result of the increased sensitivity and specificity of the quantitative assay we employed, in contrast to the methods used in previous studies (long PCR or semi-quantitative PCR methods). Our finding is also biologically plausible, due to the fact that cancer cells are metabolically adapted for rapid growth and proliferation under conditions of low pH and oxygen tension, solid cancer cells generate energy by glycolysis in strong preference to oxidative phosphorylation (33)(34)(35). Furthermore, previous in vitro studies have suggested that mitochondrial protein synthesis is defective and the activity of cytochrome oxidase decreases when the proportion of the mtDNA 4977 mutation was greater than 60% in the cancer cell (23).…”
Section: Discussionmentioning
confidence: 67%
“…We believe the higher detection rate for the mtDNA 4977 mutation in our study is a result of the increased sensitivity and specificity of the quantitative assay we employed, in contrast to the methods used in previous studies (long PCR or semi-quantitative PCR methods). Our finding is also biologically plausible, due to the fact that cancer cells are metabolically adapted for rapid growth and proliferation under conditions of low pH and oxygen tension, solid cancer cells generate energy by glycolysis in strong preference to oxidative phosphorylation (33)(34)(35). Furthermore, previous in vitro studies have suggested that mitochondrial protein synthesis is defective and the activity of cytochrome oxidase decreases when the proportion of the mtDNA 4977 mutation was greater than 60% in the cancer cell (23).…”
Section: Discussionmentioning
confidence: 67%
“…To test this, cells were incubated in a medium containing galactose in which cell growth depends on functional oxidative phosphorylation. 40 As a control, cells were grown in normal glucose-containing medium in which energy production occurs mainly via glycolysis. Strikingly, in the absence of CL, cells were unable to grow in galactose medium (Figure 2c), which points to a defective mitochondrial respiratory chain.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to low ADP and minimal O 2 consumption. Further evidence that mitochondria remodel according to changes in OXPHOS activity came from the work of Rossignol et al (2004) who showed that the mitochondrial network extended within cells and became more ramified and interconnected in the presence of galactose.…”
Section: Mitochondrial Physiology In Cell Proliferation and Tumour Prmentioning
confidence: 99%